Geotechnical parameters of iron ore tailings from the Quadrilátero Ferrífero after different treatments and ore processing - Silva, JPS; Mendes, MB; Milonas, JG; Pirete, W; Souza, WJ (Paste 2013: Proceedings of the 16th International Seminar on Paste and Thickened Tailings, 2013)
The first industrial iron ore extraction in Brazil occurred in the Quadrilátero Ferrífero. Those areas most conducive to tailings disposal have been occupied over many years of operation; in the remaining areas there are many constraints that greatly hamper conventional tailings disposal. The need to reconcile tailings disposal and mining activities with lower environmental and social impacts has led to the increased national importance of new methods of disposal. Among the most promising of these methods studied in Quadrilátero Ferrífero is dewatering (cycloning, thickening, or filtering). Paste formation and tailings screening have also been studied. There is, however, a lack of information on the geotechnical parameters of the structures built with these methodologies. In the context of this search for alternatives for the disposal of tailings generated in the iron ore beneficiation process, the company Vale S.A. has conducted pilot studies and bench testing, and has evaluated the conditions for dewatering of tailings. All of this work was focused on tailings generated in the ore beneficiation plants in the Quadrilátero Ferrífero region with the greatest environmental, spatial, and topographical restrictions. The significant reduction of the richest ore, hematite, and the growing exploitation of itabirite, along with an increasing demand for iron ore, have led to a substantial increase in the volume of tailings generated in the region. The average life of the tailings containment structures is naturally reduced, and some other methods of disposal are economically infeasible. This paper aims to contribute to alternative studies and conceptual designs for new ventures by presenting data regarding the process of dewatering the tailings held by Vale S.A. It presents a consolidation of the geotechnical parameters obtained from laboratory samples collected from bench tests and pilots, and notes prospects for tailings disposal in the Quadrilátero Ferrífero region.